PENGGUNAAN AL-LAGZU FÎ AL-JAWÂB DALAM AL-QUR’AN - Nugraha, Inggo; Ali, Mad (Departemen Pendidikan Bahasa Arab, 2020)
This research article aims to describe the form of the expression al-lagzu fî al-jawâb in the Qur'an. Al-lagzu fî al-jawâb is a form of diverting the conversation to something more important. Al-lagzu fî al-jawâb is an art in balagah because it gives a beautiful impression on someone's conversation. This discussion of al-lagzu fî al-jawâb is not given a specific foundation by the scholars of balagah and the writers of the book in which discussing al-lagzu fî al-jawâb . The data source of this study was taken from the Qur'an. The object of his research is focused on the verses of al-lagzu fî al-jawâb contained in the Qur'an. The data is collected through documentation and recording format. Then the data were analyzed qualitatively. The results showed that there were eighty expressions of al-lagzu fî al-jawâb in the Qur'an. The phrase can be classified into four forms and six themes.